Identification of determinants for tRNA substrate recognition by Escherichia coli C/U34 2′-O-methyltransferase - Zhou, Mi (RNA Biol, 2015)
Post-transcriptional modifications bring chemical diversity to tRNAs, especially at positions 34 and 37 of the anticodon stem-loop (ASL). TrmL is the prokaryotic methyltransferase that catalyzes the transfer of the methyl group from S-adenosyl-L-methionine to the wobble base of tRNA(Leu)(CAA) and tRNA(Leu)(UAA) isoacceptors. This Cm34/Um34 modification affects codon-anticodon interactions and is essential for translational fidelity. TrmL-catalyzed 2′-O-methylation requires its homodimerization; however, understanding of the tRNA recognition mechanism by TrmL remains elusive. In the current study, by measuring tRNA methylation by TrmL and performing kinetic analysis of tRNA mutants, we found that TrmL exhibits a fine-tuned tRNA substrate recognition mechanism. Anticodon stem-loop minihelices with an extension of 2 base pairs are the minimal substrate for EcTrmL methylation. A35 is a key residue for TrmL recognition, while A36-A37-A38 are important either via direct interaction with TrmL or due to the necessity for prior isopentenylation (i(6)) at A37. In addition, TrmL only methylates pyrimidines but not purine residues at the wobble position, and the 2′-O-methylation relies on prior N(6)-isopentenyladenosine modification at position 37.